Communicative Competencies and Pre-Service Teaching Performance: Basis for Communication Skills Enhancement - Lilian Dela Cruz (JPAIR, 2019)
With the current demand standard for teachers equipped with the 21st-century skill of communicative competence, teacher education institutions like the DalubhasaanngLunsodng San Pablo (DLSP) have continuously searched for ways and means to fortify the communication skills development of their students and to hone them into well-prepared and well-equipped future teachers. The pre-service teaching internship is an avenue to establish the readiness of the student-teacher in an educational environment. This paper assessed the extent of association between the level of communicative competencies and pre-service teaching performance of the DLSP student teachers for the academic year 2017-2018. More specifically, it showed the profile of the pre-service teachers: the majority are aged 21-25, females, taking BEED-General Curriculum. The pre-service teachers are found to have an above-average level of communicative competencies in reading, listening, and writing but only an average level of communicative competencies in speaking. There is a significant difference among speaking, reading, and writing competencies when grouped according to major or area of specialization. There is a weak correlation between communicative competencies of listening, reading, and writing, and student teaching performance, while there is a moderate correlation between speaking competencies and student teaching performance. To get a more conclusive correlation between competencies and performance, it is recommended for the institution to include communicative competencies as one of the specific parameters in evaluating pre-service teaching performance. This study found a need to enhance the communicative competencies, especially in speaking and writing that an integrated listening, speaking, reading, and writing (LSRW) program.